1989
DOI: 10.1099/0022-1317-70-4-869
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Herpes Simplex Virus Type 1 Thymidine Kinase in Pathogenesis

Abstract: SUMMARYA genetically engineered herpes simplex virus type 1 (HSV-1) thymidine kinase (TK) deletion mutant has been constructed and used to investigate the role of this gene in pathogenesis. Inoculation of mice with the HSV TK deletion mutant resulted in the establishment of latent ganglionic infection as demonstrated by superinfection of explanted ganglia with wild-type (wt) virus bat not by routine explant culture suggesting that the virus-encoded TK is not essential for the establishment of latent infection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
162
1

Year Published

1991
1991
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 218 publications
(176 citation statements)
references
References 34 publications
(26 reference statements)
13
162
1
Order By: Relevance
“…Two classes of vectors have been utilised in these studies: (1) replication-defective vectors lacking both the essential glycoprotein H (gH) gene 22 and the nonspecific neurovirulence determinant encoded by the thymidine kinase (tk) gene 23 and (2) a virus mutant severely impaired for immediate early (IE) gene expression designated in1388. 20 gH is essential for virus entry and cell-to-cell spread.…”
Section: Cs1 and Cs5 Have The Same Deletion Of The Viral Genome Betwementioning
confidence: 99%
“…Two classes of vectors have been utilised in these studies: (1) replication-defective vectors lacking both the essential glycoprotein H (gH) gene 22 and the nonspecific neurovirulence determinant encoded by the thymidine kinase (tk) gene 23 and (2) a virus mutant severely impaired for immediate early (IE) gene expression designated in1388. 20 gH is essential for virus entry and cell-to-cell spread.…”
Section: Cs1 and Cs5 Have The Same Deletion Of The Viral Genome Betwementioning
confidence: 99%
“…The former mechanism is most frequently seen in the clinic (8,16,17,29), probably because TK is not essential for viral replication in most tissues and culture cells (36). However, several reports have demonstrated that TK activity facilitates HSV reactivation from latency in neural ganglia (11,13,44,46).…”
mentioning
confidence: 99%
“…The former mechanism is most frequently seen in the clinic (8,16,17,29), probably because TK is not essential for viral replication in most tissues and culture cells (36). However, several reports have demonstrated that TK activity facilitates HSV reactivation from latency in neural ganglia (11,13,44,46).Changes in the TK gene can result in viruses producing no or partial amounts of TK or with an altered substrate specificity (4, 23). Darby et al have proposed a preliminary model for the active center of the HSV type 1 (HSV-1) TK enzyme including three distinct regions: an ATP-binding site (amino acids 51 to 63), a nucleoside-binding site (amino acids 168 to 176), and amino acid 336 (12).…”
mentioning
confidence: 99%
“…TK synthesized by alphaherpesviruses appears to facilitate the growth of virus in non-dividing cells [25]. Many recent investigations have demonstrated that TK deficient mutants of herpes simplex virus type 1 (HSV-1) [25], PRV [49,112], BHV-1 [50], equine herpesvirus type 1 (EHV-1) [101], and FHV-1 [131] are remarkably attenuated for their natural hosts or mice and appear to be less readily reactivated from neurons [21]. Kit et al reported the loss of ability of BHV-1 TK deficient mutant to infect the fetus and to cause abortions [51] and the reduction of ability of the mutant to develop latent infections [50].…”
Section: ) Tk Genementioning
confidence: 99%